Answer

Verified

86.7k+ views

Hint – In this question first compute the total number of games played by each of these 10 players and it will be (10-1=9). Now each player plays against one another and a match is held between two so find the total number of games. Since no match can end in a draw, the sum of winning and losing for a particular ${i^{th}}$ player will be equal to the total game that can be played by a single player. This concept will help getting the right option.

Complete step-by-step answer:

There are a total of 10 players.

So each player will play (10 – 1) = 9 games.

Now there are 10 players and a game of chess is played between two candidates and it is given that each player will play against every other player so the total number of games = ${}^{10}{C_2} = \dfrac{{10!}}{{2!\left( {10 - 2} \right)!}} = \dfrac{{10 \times 9 \times 8!}}{{2 \times 1 \times 8!}} = 45$

Now $w_1, w_2, ......., w_{10}$ and $l_1, l_2, ....., l_{10}$ are the number of games won and lost by players 1, 2, ...., 10 respectively.

Now each player plays 9 games without any draws.

Hence,

${w_i} + {l_i} = 9$....................... (1) (i.e. it’s the sum of winning and losing a game for a particular ith player is equal to 9).

Now the total number of wins = total number of losses.

$ \Rightarrow \sum {{w_i} = \sum {{l_i}} } $....................... (2)

Now apply summation on both sides in equation (1) we have,

$ \Rightarrow \sum {\left( {{w_i} + {l_i}} \right)} = \sum 9 $

$ \Rightarrow \sum {{w_i} + \sum {{l_i} = 9\left( {10} \right) = 90} } $ , as there are total 10 players therefore, \[\sum 9 = 9\left( {10} \right) = 90\]

Now from equation (2) we have,

$ \Rightarrow \sum {{w_i} + \sum {{w_i} = 90} } $

$ \Rightarrow \sum {{w_i}} = \dfrac{{90}}{2} = 45$

Hence,

$\sum {{w_i} = \sum {{l_i} = 45} } $......................... (3)

Now from equation (1) we have,

$ \Rightarrow {w_i} = 9 - {l_i}$

Now squaring on both sides we have,

$ \Rightarrow {\left( {{w_i}} \right)^2} = {\left( {9 - {l_i}} \right)^2}$

Now expand the square according to property ${\left( {a - b} \right)^2} = {a^2} + {b^2} - 2ab$ so we have,

$ \Rightarrow {\left( {{w_i}} \right)^2} = {9^2} + {\left( {{l_i}} \right)^2} - 18{l_i}$

Now take summation on both sides we have,

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = \sum {\left( {{9^2} + {{\left( {{l_i}} \right)}^2} - 18{l_i}} \right)} $

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = \sum {81} - 18\sum {\left( {{l_i}} \right)} + \sum {{{\left( {{l_i}} \right)}^2}} $

Now there are total 10 players

Therefore $\sum {81} = 81\left( {10} \right) = 810$

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = 810 - 18\sum {\left( {{l_i}} \right)} + \sum {{{\left( {{l_i}} \right)}^2}} $

Now from equation (3) we have,

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = 810 - 18\left( {45} \right) + \sum {{{\left( {{l_i}} \right)}^2}} $

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = 810 - 810 + \sum {{{\left( {{l_i}} \right)}^2}} $

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = \sum {{{\left( {{l_i}} \right)}^2}} $

So this is the required answer.

Hence option (A), (B) and (D) are correct.

Note – Now as the matches proceed the total number of winning has to be equal to the total number of losing , as when a match is played between two players there can only be two outcomes either person one wins and person 2 loses or person 1 loses and person 2 wins. Since the drawn cases need not to be taken into consideration thus under this circumstance only this equation holds true, and it’s the trick point of this problem.

Complete step-by-step answer:

There are a total of 10 players.

So each player will play (10 – 1) = 9 games.

Now there are 10 players and a game of chess is played between two candidates and it is given that each player will play against every other player so the total number of games = ${}^{10}{C_2} = \dfrac{{10!}}{{2!\left( {10 - 2} \right)!}} = \dfrac{{10 \times 9 \times 8!}}{{2 \times 1 \times 8!}} = 45$

Now $w_1, w_2, ......., w_{10}$ and $l_1, l_2, ....., l_{10}$ are the number of games won and lost by players 1, 2, ...., 10 respectively.

Now each player plays 9 games without any draws.

Hence,

${w_i} + {l_i} = 9$....................... (1) (i.e. it’s the sum of winning and losing a game for a particular ith player is equal to 9).

Now the total number of wins = total number of losses.

$ \Rightarrow \sum {{w_i} = \sum {{l_i}} } $....................... (2)

Now apply summation on both sides in equation (1) we have,

$ \Rightarrow \sum {\left( {{w_i} + {l_i}} \right)} = \sum 9 $

$ \Rightarrow \sum {{w_i} + \sum {{l_i} = 9\left( {10} \right) = 90} } $ , as there are total 10 players therefore, \[\sum 9 = 9\left( {10} \right) = 90\]

Now from equation (2) we have,

$ \Rightarrow \sum {{w_i} + \sum {{w_i} = 90} } $

$ \Rightarrow \sum {{w_i}} = \dfrac{{90}}{2} = 45$

Hence,

$\sum {{w_i} = \sum {{l_i} = 45} } $......................... (3)

Now from equation (1) we have,

$ \Rightarrow {w_i} = 9 - {l_i}$

Now squaring on both sides we have,

$ \Rightarrow {\left( {{w_i}} \right)^2} = {\left( {9 - {l_i}} \right)^2}$

Now expand the square according to property ${\left( {a - b} \right)^2} = {a^2} + {b^2} - 2ab$ so we have,

$ \Rightarrow {\left( {{w_i}} \right)^2} = {9^2} + {\left( {{l_i}} \right)^2} - 18{l_i}$

Now take summation on both sides we have,

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = \sum {\left( {{9^2} + {{\left( {{l_i}} \right)}^2} - 18{l_i}} \right)} $

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = \sum {81} - 18\sum {\left( {{l_i}} \right)} + \sum {{{\left( {{l_i}} \right)}^2}} $

Now there are total 10 players

Therefore $\sum {81} = 81\left( {10} \right) = 810$

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = 810 - 18\sum {\left( {{l_i}} \right)} + \sum {{{\left( {{l_i}} \right)}^2}} $

Now from equation (3) we have,

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = 810 - 18\left( {45} \right) + \sum {{{\left( {{l_i}} \right)}^2}} $

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = 810 - 810 + \sum {{{\left( {{l_i}} \right)}^2}} $

$ \Rightarrow \sum {{{\left( {{w_i}} \right)}^2}} = \sum {{{\left( {{l_i}} \right)}^2}} $

So this is the required answer.

Hence option (A), (B) and (D) are correct.

Note – Now as the matches proceed the total number of winning has to be equal to the total number of losing , as when a match is played between two players there can only be two outcomes either person one wins and person 2 loses or person 1 loses and person 2 wins. Since the drawn cases need not to be taken into consideration thus under this circumstance only this equation holds true, and it’s the trick point of this problem.

Recently Updated Pages

Name the scale on which the destructive energy of an class 11 physics JEE_Main

Write an article on the need and importance of sports class 10 english JEE_Main

Choose the exact meaning of the given idiomphrase The class 9 english JEE_Main

Choose the one which best expresses the meaning of class 9 english JEE_Main

What does a hydrometer consist of A A cylindrical stem class 9 physics JEE_Main

A motorcyclist of mass m is to negotiate a curve of class 9 physics JEE_Main

Other Pages

The thickness of the depletion layer is approximately class 11 physics JEE_Main

If a wire of resistance R is stretched to double of class 12 physics JEE_Main

Derive an expression for maximum speed of a car on class 11 physics JEE_Main

Electric field due to uniformly charged sphere class 12 physics JEE_Main

Velocity of car at t 0 is u moves with a constant acceleration class 11 physics JEE_Main